2021
DOI: 10.2147/copd.s300299
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Treatment Recommendations for Chronic Obstructive Pulmonary Disease - Results from the Swedish National Airway Register

Abstract: Introduction Swedish guidelines adhere to the international GOLD document regarding management of chronic obstructive pulmonary disease (COPD). Based on data from the Swedish National Airway Register (SNAR) the aim was to evaluate adherence to guidelines of pharmacological treatment of COPD in Swedish primary and secondary care. Methods During a period of 18 months, data on symptoms (CAT, mMRC), lung function, exacerbation history and pharmacological treatment from 15,5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
0
10
0
2
Order By: Relevance
“…In addition, results from the Taiwan obstructive lung disease (TOLD) study revealed that about one-third of Group A/B patients are prescribed with ICS-containing therapy [41]. In another study based on data from the Swedish National Airway Register(SNAR), about 33% of Group A and 46% of Group B patients were treated with ICS, suggesting a high use of ICS containing therapy [42]. In order to optimize the treatment in patients with COPD, factors such as high blood eosinophil counts or fractional exhaled nitric oxide (FeNO) levels, a past medical history of asthma or allergic rhinitis or findings suggestive of asthma-COPD overlap (ACO) should be considered to identify patients who would benefit from ICS use [10,43,44].…”
Section: Table 3 Baseline Characteristics Copd Severity and Prescribe...mentioning
confidence: 99%
“…In addition, results from the Taiwan obstructive lung disease (TOLD) study revealed that about one-third of Group A/B patients are prescribed with ICS-containing therapy [41]. In another study based on data from the Swedish National Airway Register(SNAR), about 33% of Group A and 46% of Group B patients were treated with ICS, suggesting a high use of ICS containing therapy [42]. In order to optimize the treatment in patients with COPD, factors such as high blood eosinophil counts or fractional exhaled nitric oxide (FeNO) levels, a past medical history of asthma or allergic rhinitis or findings suggestive of asthma-COPD overlap (ACO) should be considered to identify patients who would benefit from ICS use [10,43,44].…”
Section: Table 3 Baseline Characteristics Copd Severity and Prescribe...mentioning
confidence: 99%
“…Важным шагом в упрощении лечения ХОБЛ и улучшении приверженности назначенной терапии является снижение частоты приема доз до минимума, необходимого для поддержания контроля заболевания [19]. Поэтому возможность применять одну дозу один раз в день является важной стратегией для улучшения приверженности к соблюдению лечебного режима [19][20][21][22][23].…”
Section: принципы терапии стабильной хронической обструктивной болезн...unclassified
“…Эти комбинации показали преимущество перед своими монокомпонентами и плацебо по влиянию на объем форсированного выдоха за первую секунду (ОФВ 1 ). При этом эксперты GOLD признают, что сочетание бронхолитиков с разным механизмом действия может повысить эффективность бронходилатации при равном или даже меньшем количестве побочных эффектов [21][22][23]. Предложено несколько объяснений преимущества такой комбинации.…”
Section: принципы терапии стабильной хронической обструктивной болезн...unclassified
“… 7 Results from the Swedish National Airway Register showed that in GOLD Groups A, and B patients, 19%, and 34%, respectively, received such therapy. 8 …”
Section: Introductionmentioning
confidence: 99%